Dnazymes As Novel Therapeutics - K.BABUNAGESWARARAO; R.RAMAKRISHNA; P.D.KAMAL KUMAR; SYED SAMEER (International Journal of Pharma and Bio Sciences, 2011)
DNAzymes are the catalytic DNA molecules which are single stranded with enzymatic activity. Many deoxyribozymes catalyses DNA phosphorylation, DNA adenylation, DNA deglycosylation, porphyrin metallation, thymine dimer photo reversion and DNA cleavage, act as catalysts in asymmetric synthesis. 10–23 DNAzymes are known for their excellent catalytic efficiency. Similar to other antisense molecules, DNAzymes are prone to nucleolytic degradation in body fluids. To prolong the half-life of oligonucleotides for in-vivo usage, to enhance biostability, to reduce toxicity and improve target affinity modified nucleotides are usually incorporated. Even with certain advantages and limitations for DNAzymes, they find wide applications in medicine and therapeutics like in cardiovascular, cancer, anti-bacterials, pain, brain disorders etc. In present study we have focused on the structure of first DNAzyme, its advantages, and various applications of the DNAzymes.